Evaluation of the pharmacokinetic and pharmacodynamic drug interactions between cilnidipine and valsartan, in healthy volunteers - Lee J; Lee H; Jang K; Lim KS; Shin D; Yu KS (Dove Medical Press, 2014)
Jieon Lee,1,* Howard Lee,2,* Kyungho Jang,1 Kyoung Soo Lim,3 Dongseong Shin,1 Kyung-Sang Yu11Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Clinical Trials Center, Seoul National University Hospital, Seoul, Republic of Korea; 3Department of Clinical Pharmacology and Therapeutics, CHA University School of Medicine and CHA Bundang Medical Center, Seongnam, Republic of Korea *These authors contributed equally to this workPurpose: Although cilnidipine and valsartan are widely coadministered to patients with hypertension, their drug–drug interaction potential has not been investigated. This study compared the pharmacokinetic (PK), pharmacodynamic (PD), and tolerability profiles of cilnidipine and valsartan, both alone and in combination, in healthy male subjects.Patients and methods: Fifty-four subjects, enrolled into an open-label, single-dose, three-treatment, three-period crossover study, randomly received cilnidipine (10 mg), valsartan (160 mg), or both according to one of six sequences. Blood samples were collected at baseline and up to 24 hours after drug administration in each period. Plasma concentrations of cilnidipine and valsartan were determined by liquid chromatography with tandem mass spectrometry. Maximum plasma concentration (Cmax) and area under the concentration-time curve from 0 to the last measurable time (AUClast) were estimated using a noncompartmental method. Tolerability was evaluated by assessing adverse events (AEs), vital signs, electrocardiograms, and clinical laboratory tests. Blood pressure was also measured for PD assessment.Results: A total of 51 subjects completed the study. The PK profile of cilnidipine was not significantly affected by coadministered valsartan; the geometric mean ratio and 90% confidence interval (90% CI) of AUClast for cilnidipine with and without valsartan was 1.04 (0.98–1.10). Likewise, cilnidipine did not affect the PK of valsartan; the geometric mean ratio (90% CI) of AUClast for valsartan with and without cilnidipine was 0.94 (0.83–1.07). Coadministration of cilnidipine and valsartan reduced blood pressure in an additive way. No serious AEs were reported, and both cilnidipine and valsartan were well tolerated.Conclusion: Coadministered cilnidipine and valsartan do not cause a significant PK or PD interaction, and they are well tolerated.Keyword: antihypertensive drugs